Housing Finance and Inclusive Growth in Africa: Benchmarking, Determinants and Effects - (:unkn) unknown (My University, 2021)
Using a panel database of 48 Sub-Saharan African countries from 2000 to 2012 that we partially constructed, this paper analyses the structure of housing finance in Africa, its determinants, and its impact on inclusive growth. We find that market capitalization and urbanization are key positive determinants of housing finance, while a post-conflict environment is conducive to greater housing finance development. This result suggests that housing finance is driven by standard market forces of demand and supply. Besides, we find that housing finance development in Africa is not yet an effective tool for reducing economic inequality, at its current, very earlier stage. However, we show that above a given threshold, housing finance could be efficient at reducing inequality. Finally, there is a slightly positive relationship between housing finance and greater economic development in Africa. All these findings suggest that policies to boost housing finance development in Africa would be fruitful in the medium to long terms.
Keywords: African Research